Research on the Path of Recommendation Algorithm Empowering Ideological and Political Education in Colleges and Universities - Meng, Di; Wei, Shangli (Journal of Social Science and Humanities, 2025)
In the era of artificial intelligence, recommendation algorithms have reconstructed the network information dissemination environment and have had a huge impact on the ideological and political education of colleges and universities. As an important technology for information distribution and personalized services, recommendation algorithms can accurately identify the ideological characteristics and personalized needs of the subjects of ideological and political education in colleges and universities, improve the pertinence, effectiveness and coordination of educational activities, and well empower the ideological and political education of colleges and universities. This paper first summarizes the concept and characteristics of recommendation algorithms, then examines the opportunities for recommendation algorithms to empower ideological and political education in colleges and universities; then studies the dilemma of recommendation algorithms in empowering ideological and political education in colleges and universities; finally, the empowerment path is explored, in order to provide theoretical support and practical reference for the high-quality development of ideological and political education in colleges and universities.